Macroeconomic effects of fiscal policies: Empirical evidence from Bangladesh, China, Indonesia and the Philippines - Geoffrey Ducanes; Marie Anne Cagas; Duo Qin; Pilipinas F. Quising; Mohammad Abdur Razzaque (Queen Mary University of London, Department of Economics, 2006)
This paper studies macroeconomic effects of fiscal policies in four Asian countries - Bangladesh, China, Indonesia, and the Philippines - by means of structural macroeconometric model simulations. It is found that short-term fiscal multipliers from an untargeted increase in government expenditure are positive but much less than those from an increased expenditure targeted to capital spending. The multiplier effects from fiscal expansion via a tax rate reduction are found to be typically much less than through higher spending. The effectiveness of automatic stabilizers in general, and more specifically whether expenditure or tax-side stabilizer is more effective, differs across countries.
Keywords: E62; E17; C53; P52; 330; Fiscal policy; Growth; Public finance; Deficit